Linking Lipid Profile to Stress Urinary Incontinence in US Women: A National Cross-Sectional Study - Lu M; Zhang Y; Yang Q; Huang J; Deng K (International Journal of Women's Health)
Mingjing Lu, Yingshan Zhang, Qian Yang, Jinfa Huang, Kaixian Deng Department of Gynecology, The Eighth Affiliated Hospital, Southern Medical University (The First People’s Hospital of Shunde Foshan), Foshan, 528308, People’s Republic of ChinaCorrespondence: Kaixian Deng, Email nsyfek@163.comObjective: Stress urinary incontinence (SUI) is a common pelvic floor disorder in women, yet the role of lipid metabolism in its occurrence remains unclear. This study investigated the association between lipid parameters and SUI in women.Methods: This study analyzed data from the 2005– 2018 National Health and Nutrition Examination Survey (NHANES), including 7,892 women. SUI was identified via questionnaire, and lipid levels were measured using standardized laboratory methods. Weighted multivariable logistic regression examined the association between lipid levels and SUI, while restricted cubic splines (RCS) assessed potential nonlinear relationships. Subgroup analyses explored effect modifications.Results: Higher remnant cholesterol (RC), total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) were significantly associated with increased SUI risk (P < 0.05), with a significant positive trend (P for trend < 0.05). RCS analysis indicated a linear relationship between RC and SUI, while TC and LDL-C showed nonlinear associations with inflection points at 4.97 and 2.85 mmol/L, respectively. High-density lipoprotein cholesterol (HDL-C) exhibited a U-shaped relationship, with the lowest SUI risk at 1.47 mmol/L. Subgroup analyses showed stronger associations for RC in women < 65 years and those without hypertension, while TC and LDL-C had a greater impact in women without hypertension or oral contraceptive use.Conclusion: Elevated RC, TC, and LDL-C may increase SUI risk, while both low and high HDL-C levels may also contribute. These findings highlight the role of lipid metabolism in SUI and support early screening and metabolic intervention strategies.Keywords: stress urinary incontinence, remnant cholesterol, total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, NHANES